Youth on social media: unveiling natural disasters information seeking factors - Maliki, Maisarah; Bolong, Jusang; Ahmad Ghazali, Akmar Hayati (Human Resource Management Academic Research Society, 2024)
Information seeking on social media has now become a habitual desire of social media users including youth as the most active and interactive users. This study was conducted to unveil potential factors of natural disasters information seeking among youth on social media. A self- administered survey was conducted to collect data for instrument testing. Questionnaires were distributed to 500 youth from five zones in Malaysia. This study contributes to the field of environmental and behavioral research by focusing on the potential factors of natural disasters information seeking among youth on social media; namely social tie variety, heuristic, information quality, social motivation and cognitive homogeneity. This study also line out practical implications on youth and social media users especially when focused research is conducted in the behavioral study of social media use by youth. The results show that youth have social tie variety, heuristic, information quality, social motivation and cognitive homogeneity as natural disasters information seeking factors in using social media. All factors show a high correlation among youth except for correlation of cognitive homogeneity that is moderate, yet still significant. A systematic natural disasters information seeking system in social media is in great demand along progressive modern era. Therefore, the role of natural disasters information seeking factors need to be unveil for better understanding through longitudinal studies and experiments which is behavior related.